A exposição crônica ao mercúrio agrava os efeitos do infarto agudo do miocárdio em ratos - Souza, Keren Alves de (2022)
Environmental contamination has exposed humans to metal agents, including mercury (Hg). Studies suggest that chronic exposure to Hg can affect the cardiovascular system. However, the present study evaluated whether chronic exposure to Hg can increase mortality due to arrythmias in rats underwent Myocardial Infarction (MI). Methods: Male rats (12 weeks old) were divided into four groups: SHAM + Sal, SHAM + Hg, MI + Sal, and MI + Hg. Animals received i.m injections of HgCl2 (1st dose 4.6μg/kg, subsequent dose 0.07μg/kg/day to cover daily loss) or vehicle-saline (Sal) for three weeks. At the end of the third week, the animals were submitted to infarction surgery through of ligation of the anterior descending left coronary artery. SHAMs were submitted the same procedure except to coronary ligation. Electrocardiographic (ECG) recordings were performed 5 minutes before and 20 minutes after surgeries. Number of ventricular extra systoles (VES); duration of ventricular tachycardia (VT) and atrioventricular blocks (AVB) were analyzed. One week after MI, hemodynamic measurements were performed and ponderal data were analyzed. Also, levels of the reactive oxygen species (ROS) superoxide anion (O2-) and nitric oxide (NO) in the cardiac muscle of the animals were performed through fluorescence analyses using Dihydroethidium (DHE) and Diaminofluorescein (DAF), respectively. The protocol was approved by CEUA (20/2018 and 24/2020). The scar size was not different between MI groups. The mortality rate in MI + Hg was 31.82% while MI + Sal was 21.43%. ECG recordings showed an increase in AVB in IM groups (min: SHAM + Sal = 0.00±0.00%; SHAM + Hg = 0.81 ± 0.67%; MI + Sal = 4.35 ± 0.96%*#; MI + Hg = 3.64 ± 0.88%*#; *p < 0.05 vs SHAM + Sal, #p < 0.05 vs SHAM + Hg). Basckó coefficient showed that arrhythmias after MI were aggravated by exposure to Hg (SHAM + Sal = 0.24 ± 0.19; SHAM + Hg = 0.75 ± 0.35; MI + Sal = 2.97 ± 0.30*#; MI + Hg = 4.00 ± 0.21*#+; *p < 0.05 vs SHAM + Sal, #p < 0.05 vs SHAM + Hg, +p<0.05vsMI+Sal). Also, there was strong correlation between mortality and AVB (r=0.7379), VES (r=0.9487), VT (r=0.9487) and Basckó coefficient (r=0,9487). SHAM + Hg group has increased of the systolic blood pressure, however these values were decreased in IM groups (mmHg: SHAM + Sal = 105 ± 2.98; SHAM + Hg = 115±3.71*; MI + Sal = 95.47 ± 3.58*#; MI + Hg = 90.01 ± 2.96*#; *p < 0.05 vs SHAM + Sal, #p < 0.05 vs SHAM + Hg). Left Ventricle end Diastolic Pressure was increased in MI + Sal group (SHAM + Sal = 7.31 ± 1.25; SHAM + Hg = 5.38 ± 1.44; MI + Sal = 15.95 ± 2.84*#; MI + Hg = 9.56 ± 1.38+; *p < 0.05 vs SHAM + Sal, #p<0.05vsSHAM+Hg, +p<0.05vsMI+Sal). dP/dt+ and dP/dt- values, were decreased in IM groups (dP/dt+ in mmHg :SHAM + Sal = 5515±543; SHAM + Hg = 5779 ± 728; MI + Sal = 3623 ± 315*#; MI + Hg = 2782 ± 322*#; dP/dt- in mmHg: SHAM + Sal = -3500 ± 403; SHAM + Hg = -3180 ± 354; MI + Sal = -2248 ± 122*#; MI + Hg = -1833 ± 125*#; *p < 0.05 vs SHAM + Sal, #p < 0.05 vs SHAM + Hg). The heart weight and body weight ratio was increased in IM groups (SHAM + Sal = 2,82 ± 0,04; SHAM + Hg = 2,87 ± 0,12; MI + Sal = 3,83 ± 0,26*#; MI + Hg = 3,73 ± 0,22*#; *p < 0,05 vs SHAM + Sal, #p < 0.05 vs SHAM + Hg) as well as the lung weight and body weight ratio (SHAM + Sal = 5,11 ± 0,19; SHAM + Hg = 4,69 ± 0,17; MI + Sal = 8,97 ± 0,79*#; MI + Hg = 7,50 ± 0,67*#+; *p < 0,05 vs SHAM + Sal, #p < 0.05 vs SHAM + Hg, +p < 0,05 vs MI + Sal). ROS levels were higher in groups that associated exposed to Hg and IM (O2- in a.u: SHAM + Sal = 1.79 ± 1.79; SHAM + Hg = 58.88 ± 6.01; MI + Sal = 171 ± 7.26*#; MI + Hg = 221 ± 12.14*#; NO in a.u: SHAM + Sal = 57,27 ± 8.05; SHAM + Hg = 106 ± 10.97; MI + Sal = 207 ± 8.87*#; MI + Hg = 246 ± 4.54*#+; *p< 0.05 vs SHAM + Sal, #p < 0.05 vs SHAM + Hg, +p< 0.05 vs MI + Sal). Mercury intoxication caused more arrhythmias in infarcted animals, increased ROS and changed pressure parameters. These results suggest a worsening of cardiac events triggered by MI, as well as increased mortality after the injury.